You're Worried, We're Listening: Online Testing of the Effectiveness of Education Materials to Improve Consumer Knowledge and Confidence in Reporting Patient Deterioration. Issue 8 (27th December 2021) - King, Lindy; Ullah, Shahid; Belan, Ingrid; Clark, Robyn A.; Young, Tom; Grantham, Hugh; Peacock, Guy; Kidd, Michael R.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Early identification of patient deterioration in hospital is important to reduce mortality, avoidable morbidity, length of stay, and associated healthcare costs. By closely observing physical and behavioral changes, deteriorating patients are more likely to be identified. Patients and family at the bedside can play an important role in reporting deterioration if made aware of how to do so. Therefore, the objective of this study was to undertake an online evaluation of educational materials designed to improve consumers' knowledge and confidence to report patient deterioration. Methods: A convenience sample was used to recruit community-based participants for an online survey. A self-designed validated instrument was used to undertake a preintervention and postintervention test involving 3 types of educational materials. Quantitative data were analyzed with Wilcoxon signed rank test to compare participants' knowledge and confidence before and after exposure to the intervention. Conventional content analyses examined responses on key messages and recommendations to improve the educational materials. Results: A total of 84 respondents completed both prequestionnaires and postquestionnaires. After exposure to the education materials, analyses confirmed that knowledge and confidence scores were significantly higher than baseline measures. Content analyses indicated a clear understanding of the key messages presented in the materials. Four main recommendations were made regarding the education materials. Conclusions: Participants readily identified the key messages in the educational materials and demonstrated increased knowledge and confidence to report concerns about deterioration. Further research is required to determine the efficacy of the educational materials in relation to consumer behavior.